2012
DOI: 10.3747/co.19.905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise in reducing breast and chest-wall pain in patients with breast cancer: a pilot study

Abstract: Breast or chest-wall pain (bcp) is prevalent in 20%–50% of breast cancer survivors, and it affects quality of life (qol). To determine the feasibility and potential efficacy of an exercise program to improve patient qol and bcp, such a program was offered to breast cancer patients suffering from bcp. The study enrolled 10 breast cancer patients with moderate-to-severe bcp at 3–6 months after completion of all adjuvant treatments. These patients participated in a 12-week comprehensive health improvement program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“… 39 Another study found that exercise had several beneficial effects and mitigated chest wall pain in breast cancer patients. 40 Clinical staff could encourage patients with persistent symptoms to exercise to improve symptoms. More study is needed to develop effective strategies to manage persistent symptoms in TB patients after DOTS completion.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Another study found that exercise had several beneficial effects and mitigated chest wall pain in breast cancer patients. 40 Clinical staff could encourage patients with persistent symptoms to exercise to improve symptoms. More study is needed to develop effective strategies to manage persistent symptoms in TB patients after DOTS completion.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence has shown that rehabilitative exercise programs, which commonly include a combination of resistance training and aerobic exercises, can effectively reduce pain in breast cancer survivors. [10][11][12] Women living with breast cancer who are directed to rehabilitative exercise programs experience an improvement not only in pain levels but also in their ability to engage in activities of daily living, in their psychological health, and in their overall quality of life. [13][14][15] However, despite evidence to support exercise programs to reduce pain related to breast cancer treatment, residual pain and upper-limb discomfort are common complaints in breast cancer survivors, and there is little focus on the duration of effectiveness of such programs for reducing pain after treatment for breast cancer.…”
mentioning
confidence: 99%
“…Moreover, the 3-weeks medication scheme reminded patients in the intervention group to return the second questionnaire at the correct date. These return rates are in line with most clinical and HRQoL studies [26,32]. Higher questionnaire return rates, however, would have increased the study's ability to assess the intervention's efficacy.…”
Section: Discussionmentioning
confidence: 49%